(untitled) (The Conference Hub, 2025)
This article explores how Russian literature did not merely reflect the socio-political reality of the 19th century but actively constructed it. By synthesizing a new national language and introducing transformative social types—such as the "superfluous man" and the "little man"—writers like Alexander Pushkin, Nikolai Gogol, and Ivan Turgenev provided a profound diagnosis of societal crises and paved the moral way for the abolition of serfdom. Furthermore, the works of Fyodor Dostoevsky and Leo Tolstoy elevated literature to the status of "secular theology," offering programs for global ethical renewal and establishing a unique literary-centric culture. This study argues that the system of ethical coordinates created in the silence of writers’ offices determined the vector of Russian social thought and its integration into the universal human context.